Medieval Romance and the Construction of Heterosexuality - Sylvester, L. author. aut Link
XI, 202 p.
Keywords: This book interrogates our ideas about heterosexuality through examination of medieval romance narratives. Familiar configurations of romantic fiction such as male desire overwhelming feminine reluctance and the aloof masculine hero undone by love derive from this period. This book tests current theories of language and desire through stylistic analysis, examining transitivity choices and speech acts in sexual encounters and conversations in medieval romances. In the context of current preoccupations with gender and sexuality, and consent in rape cases, this study is of interest to scholars investigating language and sexuality as well as those researching and teaching medieval literature and culture.